The techniques obtaining critical condition for sediment particle movement - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The two important sets of measurements required for measuring initiation of sediment particle movement are pair ofsize D, of particle median axis and the critical unit water discharge qc, associated with movement of that size. Gravel has generally been neglected compared with the finer material and predictive transport models have so far had very limited success in achieving agreement with field data. Therefore, some of the aspects of natural gravel-bed rivers which affect the initiation of motion and bed load transport process, as opposed to case for artificial channels, have been studied by the author in July, 1990 and by Hofer in 1979 (personal communication) on the Pitzbach, Austria. Two techniques are used in this study to obtain the data of critical condition for sediment particle movement from the bed load transport data from the Pitzbach, Austria. The performance of the techniques which were used to obtain the data for critical condition for sediment particle movement then were assessed using existing equations of the Schocklitsch (1962), Bathurst et al (1987), Bathurst (1987) and lnpasihardjo (1991). The performance of the techniques, the comparison and calculated critical unit water discharge are discussed The results indicated that, the Schocklitsch (1962) and the Bathurst et al (1987) equations significantly underestimates qc with the Pitzbach data. The discrepancies are probably caused by the hiding/exposure effects which are not accounted for in both equations, while the Bathurst (1987) and lnpasihardjo (1991) gives a good agreement qc. One interpretation therefore is that slope is another variable which should be involved in the hiding/exposure effects for initiation of motion of non-uniform bed material. From the discussion the two techniques can be used for obtaining the critical condition for sediment particle movement from the bed load transport data.